Chimeric Structure of Plant Malic Enzyme Family: Different Evolutionary Scenarios for NAD- and NADP-Dependent Isoforms - Tronconi, Marcos A.; Andreo, Carlos S.; Drincovich, Maria F. (Frontiers in Plant Science, 2018)
Malic enzyme (ME) comprises a family of proteins with multiple isoforms located in different compartments of eukaryotic cells. In plants, cytosolic and plastidic enzymes share several characteristics such as NADP specificity (NADP-ME), oxaloacetate decarboxylase (OAD) activity, and homo-oligomeric assembly. However, mitochondrial counterparts are NAD-dependent proteins (mNAD-ME) lacking OAD activity, which can be structured as homo- and hetero-oligomers of two different subunits. In this study, we examined the molecular basis of these differences using multiple sequence analysis, structural modeling, and phylogenetic approaches. Plant mNAD-MEs show the lowest identity values when compared with other eukaryotic MEs with major differences including short amino acid insertions distributed throughout the primary sequence. Some residues in these exclusive segments are co-evolutionarily connected, suggesting that they could be important for enzymatic functionality. Phylogenetic analysis indicates that eukaryotes from different kingdoms used different strategies for acquiring the current set of NAD(P)-ME isoforms. In this sense, while the full gene family of vertebrates derives from the same ancestral gene, plant NADP-ME and NAD-ME isoforms have a distinct evolutionary history. Plant NADP-ME genes may have arisen from the α-protobacterial-like mitochondrial ancestor, a characteristic shared with major eukaryotic taxa. On the other hand, plant mNAD-ME genes were probably gained through an independent process involving the Archaeplastida ancestor. Finally, several residue signatures unique to all plant mNAD-MEs could be identified, some of which might be functionally connected to their exclusive biochemical properties. In light of these results, molecular evolutionary scenarios for these widely distributed enzymes in plants are discussed.